A genome wide association study of genetic loci that influence tumour biomarkers cancer antigen 19-9, carcinoembryonic antigen and α fetoprotein and their associations with cancer risk. Issue 1 (7th January 2013) - He, Meian; Wu, Chen; Xu, Jianfeng; Guo, Huan; Yang, Handong; Zhang, Xiaomin; Sun, Jielin; Yu, Dianke; Zhou, Li; Peng, Tao; He, Yunfeng; Gao, Yong; et al.
Abstract : Objective: Tumour biomarkers are used as indicators for cancer screening and as predictors for therapeutic responses and prognoses in cancer patients. We aimed to identify genetic loci that influence concentrations of cancer antigen 19-9 (CA19-9), carcinoembryonic antigen (CEA) and α fetoprotein (AFP), and investigated the associations between the significant single nucleotide polymorphisms (SNPs) with risks of oesophageal squamous cell (OSCC), pancreatic and hepatocellular cancers. Design: We carried out a genome wide association study on plasma CA19-9, CEA and AFP concentrations in 3451 healthy Han Chinese and validated the results in 10 326 individuals. Significant SNPs were further investigated in three case control studies (2031 OSCC cases and 2044 controls; 981 pancreatic cancer cases and 1991 controls; and 348 hepatocellular cancer cases and 359 controls). Results: The analyses showed association peaks on three genetic loci for CA19-9 ( FUT6-FUT3 at 19p13.3, FUT2 - CA11 at 19q13.3 and B3GNT3 at 19p13.1; p=1.16×10 −13 –3.30×10 −290 ); four for CEA ( ABO at 9q34.2, FUT6 at 19p13.3, FUT2 at 19q13.3 and FAM3B at 21q22.3; p=3.33×10 −22 –5.81×10 −209 ); and two for AFP ( AFP at 4q11-q13 and HISPPD2A at 15q15.3; p=3.27×10 −18 and 1.28×10 −14 ). These explained 17.14% of the variations in CA19-9, 8.95% in CEA and 0.57% in AFP concentrations. Significant ABO variants were also associated with risk of OSCC and pancreatic cancers, and AFP variants with risk of hepatocellular cancer (p<0.05). Conclusions: This study identified several loci associated with CA19-9, CEA and AFP concentrations. The ABO variants were associated with risk of OSCC and pancreatic cancers and AFP variants with risk of hepatocellular cancer.